2018
DOI: 10.1001/jamanetworkopen.2018.4777
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Differences in Temporal Synchrony Between Brain Regions in Individuals With Autism and Typical Development

Abstract: Key Points Question Do individuals with autism show atypical duration of brain functional connections? Findings In this cohort study of 52 individuals with autism and 38 typically developing participants and a replication study of 1402 participants in a brain imaging database, increased durations of functional connections in autism were found in both distributed networks and individual brain regions, which were associated with metrics of disease severity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…It is very possible that replicable results could be found when considering the very same data at a different scale or resolution, or with that data analyzed in a different way. For example, King and colleagues (King et al, 2018) found replicable atypical temporal dynamics in rs-fMRI timecourse. Holiga et al…”
Section: Discussionmentioning
confidence: 99%
“…It is very possible that replicable results could be found when considering the very same data at a different scale or resolution, or with that data analyzed in a different way. For example, King and colleagues (King et al, 2018) found replicable atypical temporal dynamics in rs-fMRI timecourse. Holiga et al…”
Section: Discussionmentioning
confidence: 99%
“…There are also other recent papers reporting variations in time‐varying patterns in autism. King et al found increased durations of functional connections in both individual brain regions and distributed networks in autism, which were associated with metrics of disease severity [King et al, ]. They used a complementary method of analysis by introducing the width of cross‐correlation curves between resting‐state fMRI time series as a metric of relative duration of synchronous activity between brain regions (“sustained connectivity”) [King & Anderson, ].…”
Section: Discussionmentioning
confidence: 99%
“…They used a complementary method of analysis by introducing the width of cross‐correlation curves between resting‐state fMRI time series as a metric of relative duration of synchronous activity between brain regions (“sustained connectivity”) [King & Anderson, ]. The persistence of brain connectivity in autism may limit the ability to rapidly shift from one brain state to another [King et al, ]. Moreover, it has been also shown that there exists a negative correlation between processing speed and sustained connectivity [King & Anderson, ].…”
Section: Discussionmentioning
confidence: 99%
“…The human neocortex has greatly expanded in size and complexity relative to that of other mammals (1,2). Along with neocortical expansion are increased abilities such as language and reasoning which are disrupted in human diseases like autism and schizophrenia (3,4). This structure contains billions of cells grouped into dozens, if not hundreds, of molecularly distinguishable cell types (5)(6)(7)(8), many with unknown roles because specific genetic tools for their study have been lacking.…”
Section: Main Textmentioning
confidence: 99%